Inflammatory bowel disease in the dog: Differences and similarities with humans - Cerquetella, Matteo (Baishideng, 2010)
Inflammatory bowel diseases (IBD) represent important chronic conditions affecting the gastrointestinal tract in man. However, similar disorders are found in several animal species and the IBD affecting dogs are particularly important. These are encompassed by an umbrella of probably several different entities with common symptoms, some of which seem to share striking similarities with human conditions. This review will focus on the actual knowledge of IBD in dogs, and attempt to identify differences and similarities with human IBD conditions.